Teacher Readinnes Of Inclussive Education in Merauke - Karlina Wong Lieung,; Sri Hanipah,; Dewi Puji Rahayu, (Technium Social Sciences Journal, 2023)
Every child has the right to a quality and equitable education, regardless of background, ability, or special needs. However, the reality on the ground shows that not all children get equal opportunities to access education that suits their uniqueness. Inclusive education is an educational approach where all students, including children with special needs, learn together in the same school environment. This study aims to describe teachers' readiness to implement inclusive education in Merauke District. The research was conducted using descriptive and qualitative methods. The subjects of the study consisted of 129 primary school teachers from various grade levels from 60 primary schools spread across Merauke district. Data collection techniques include distributing Google Forms, interviews, and observations. The validity test was carried out by triangulating techniques by comparing the results of filling out Google Forms, interviews, and observations. The results showed (1) 75.2% or 97 teachers understood the meaning of inclusive education; (2) 85.3% or 110 teachers already had information about children with special needs; (3) 47.3% or 61 teachers expressed their readiness to accept children with disabilities in their schools, with the main reason being awareness of the rights of every child in education; however, (4) 100% or all teachers who were respondents had never attended training related to the implementation of inclusive education. As a result, teacher readiness is still very low.